2017
DOI: 10.1245/s10434-017-5941-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Risk of Upstaging HER2-Positive DCIS to Invasive Breast Cancer

Abstract: The results suggest that overexpression of HER2 may serve as a biomarker for risk stratification of patients with DCIS and may help to guide treatment strategies in the future. For institutions in which HER2 testing may be performed on DCIS, patients should be counseled appropriately about the risk of upgrade to IBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Monabati et al reported that HER2-positive DCIS cases were more likely to be of high nuclear grade (18). Mustafa et al reported that HER2-positive DCIS tended to be upstaged to invasive ductal carcinoma (16). However, the targets of that report were all typed as DCIS.…”
Section: Final Diagnosis --------------------------------------------mentioning
confidence: 95%
See 1 more Smart Citation
“…Monabati et al reported that HER2-positive DCIS cases were more likely to be of high nuclear grade (18). Mustafa et al reported that HER2-positive DCIS tended to be upstaged to invasive ductal carcinoma (16). However, the targets of that report were all typed as DCIS.…”
Section: Final Diagnosis --------------------------------------------mentioning
confidence: 95%
“…The significance of HER2 overexpression in DCIS is not well defined. However, HER2 DCIS has recently been reported as an aggressive type (16)(17)(18). Monabati et al reported that HER2-positive DCIS cases were more likely to be of high nuclear grade (18).…”
Section: Final Diagnosis --------------------------------------------mentioning
confidence: 99%
“…The NCDB is a joint project of the Commission on Cancer (CoC) of the American College of Surgeons and the American Cancer Society, and all data used in this study were de-identified and met the criteria for exempt review by the University of Oklahoma Health Sciences Center Institutional Review Board (IRB# 7446). Women were selected based on a clinical stage of T1N0M0, 14 ductal histology (International Classification of Diseases for Oncology, Third Revision [ICD-O-3] codes 8022, 8035, 8500-8503, 8523), and receipt of BCS as their first treatment (Surgery of the Primary Site codes [19][20][21][22][23][24]. Only cases diagnosed and treated, all or in part, at the reporting facility were included in the final cohort.…”
Section: Cohortmentioning
confidence: 99%
“…Likewise, HER2 positivity in pure DCIS at the biopsy level seems to be associated with increased risk of synchronous invasive cancer in the subsequent resection specimen. 66 This could be due to the fact that HER2-positive invasive carcinomas have an extensive HER2-positive in situ component, 67 which is a risk factor for sampling error. However, further investigations are necessary as this upstage risk was not confirmed by others.…”
Section: Risk Assessment For Synchronous Invasion At the Biopsy Levelmentioning
confidence: 99%
“…Among them, increased stromal inflammation seems perpetually associated with increased risk for (micro‐)invasive carcinoma, but this promising histopathological feature requires further validation in larger independent patient cohorts. Likewise, HER2 positivity in pure DCIS at the biopsy level seems to be associated with increased risk of synchronous invasive cancer in the subsequent resection specimen . This could be due to the fact that HER2‐positive invasive carcinomas have an extensive HER2‐positive in situ component, which is a risk factor for sampling error.…”
Section: Introductionmentioning
confidence: 99%